Bioinspired Biomaterial Composite for All‐Water‐Based High‐Performance Adhesives. Issue 16 (3rd June 2021) - Lo Presti, Marco; Rizzo, Giorgio; Farinola, Gianluca M.; Omenetto, Fiorenzo G.
Abstract: The exceptional underwater adhesive properties displayed by aquatic organisms, such as mussels ( Mytilus spp .) and barnacles ( Cirripedia spp .) have long inspired new approaches to adhesives with a superior performance both in wet and dry environments. Herein, a bioinspired adhesive composite that combines both adhesion mechanisms of mussels and barnacles through a blend of silk, polydopamine, and Fe 3+ ions in an entirely organic, nontoxic water‐based formulation is presented. This approach seeks to recapitulate the two distinct mechanisms that underpin the adhesion properties of the Mytilus and Cirripedia, with the former secreting sticky proteinaceous filaments called byssus while the latter produces a strong proteic cement to ensure anchoring. The composite shows remarkable adhesive properties both in dry and wet conditions, favorably comparing to synthetic commercial glues and other adhesives based on natural polymers, with performance comparable to the best underwater adhesives with the additional advantage of having an entirely biological composition that requires no synthetic procedures or processing. Abstract : New mussel‐inspired, high‐performance underwater adhesive is developed using Bombyx mori silk fibroin as protein backbone and polydopamine as catechol bearing molecule. This all‐natural synthetic‐step free composition displays in lap‐shearing bonding tests underwater adhesion forces (2.6 MPa) that rival commercial synthetic adhesives.